REASONING WITH PRECEDENTS BY THE CONSTITUTIONAL COURT OF THE REPUBLIC OF LITHUANIA - Baltrimas, Johanas (Teisė, 2016)
The paper is focused on the question when Constitutional Court’s of the Republic of Lithuania precedents have to be followed and when they should be departed from. The answer is sought in the Court’s explicitly provided principles of the doctrine of precedent and cases where the Court refused to follow its precedential rules. Among these cases, most are the Court’s rulings which dealt with the issue of precedent’s applicability under very similar circumstances. In the majority of them the Court found that precedential rule in the later case had to be departed from. These cases contain several indicators which help to foresee whether the Court will follow precedential rules which it has established in its rulings: that some reasons from the previous decision cannot be used in the later case, while maintaining consistency of entire reasoning; requirements of the rule in the later case are not ignored fully, but are implemented at least to some extent. Also in dealing with the question of precedent’s applicability, it is important to bear in mind, that the Court follows its position on individual cases and position on more common aspects – with regard to that and precedent’s role in the evaluation of the later case, standard of precedent’s applicability may vary. The research leads to a conclusion that in some cases literal application of court’s explicitly formulated reasons would be inconsistent with the court’s doctrine of precedent.